STRUCTURAL ASPECTS OF PLASTICITY LOWERING OF HIGH-STRENGTH WIRE AT BIG CUMULATIVE COMPRESSIONS - V. P. Fetisov (Литьë и металлургия)
It is shown that decrease of plasticity of high-strength wire at big total cobbings is connected with reduction of mobility of dislocations in the substructure formed at loss of perlite lamellar structure.